Hydrotalcite–PLGA composite nanoparticles for loading and delivery of danshensu. Issue 37 (9th June 2020) - Pu, Lihui; Yu, Haiyan; Du, Juan; Zhang, Yanyan; Chen, Sihao
Abstract : As one of the main pharmacodynamic components present in the water-soluble components of Salvia miltiorrhiza (Danshen), danshensu (DSS) is applicable to treating cardiovascular diseases. Abstract : As one of the main pharmacodynamic components present in the water-soluble components of Salvia miltiorrhiza (Danshen), danshensu (DSS) is applicable to treating cardiovascular diseases. Nevertheless, such drawbacks as low water solubility and short half-life could reduce its bioavailability and restrict its clinical applicability. Therefore, it can be integrated into drug-carrying polymer microspheres, which is effective in improving the bioavailability of drugs. In this study, DSS was first embedded in a hydrotalcite (LDH) layer. Then, polylactic acid (PLGA) with excellent biocompatibility and biodegradability was coated on the surface. PLGA/DSS–LDH composite nanoparticles were prepared using the double emulsion (w/o/w) solvent evaporation method. As revealed by XRD and FTIR studies, success was achieved in embedding the drug DSS in the LDH layer, with the drug loading capacity of the LDH reaching 32.6%. A study was conducted on the encapsulation efficiency, surface morphology and in vitro drug release characteristics of PLGA/DSS–LDH. PLGA/DSS–LDH composite nanoparticles exhibited not only a high encapsulation efficiency but also a sustained release profile. The hemolysis assays demonstrated that the PLGA/DSS–LDH composite nanoparticles were ineffective in the induction of hemolysis, suggesting that PLGA/LDH composite nanoparticles can provide an effective controlled release drug system for pharmaceutics.